pattern of Lipid Profile in type - 2 diabetes Mellitus Patients - Haq, Amin ul; Rehman, Jamil ur; Mehmood, Rashid; Safi, Abdul Jalal; Ahmad, Zahoor; Arif, Saatea (Journal of Postgraduate Medical Institute, 2011)
To know the patte3rn of lipid profile in obese and non obese type - 2 mellitus patients as compared to a control group. One hundred (50 obese and 50 non-obese) diagnosed patients having diabetes mellitus minimum for the last three years were randomly selected form the outdoor patients department of medicine, KTH, Peshawar during the year 2002. Obesity was taken as body mass index of more than 25kg/m. One hundred healthy individuals were selected from among the staff of KMC, KCD and KTH, Peshawar to consitute the control group. they had no history of any chronic illness. Subjects suffering from cardiovascular diseases. Kidney disorder and hepatic disorders were excluded from the study. Fasting serum triglyceride, total cholesterol, HDL-C, LDL-C and VLDL-C were determined by enzymatic calorimetric method and calculated by using friedewald (1972) formula. Dyslipidemia is a significant finding in type - 2 diabetes mellitus patients.